59‐3: Fast VAN ECB Liquid Crystal on Silicon for Automotive Head Up Displays. Issue 1 (May 2017) - Shi, Liangyu; Srivastava, Abhishek Kumar; Zhang, Wanlong; Liao, Engle; Zhu, Xiuling; Chigrinov, Vladimir. G.; Kwok, Hoi Sing
Abstract : In this article, we disclose a fast VAN/ ECB liquid crystal on silicon display for head mounted displays in vehicle projections. With the 0.37 inch dimension in diagonal and 720p resolution CMOS backplane, we can achieve a fast response time less than 2.78ms at room temperature. After optimization of working mode and post annealing fabrication process to remove the rubbing muras, the reflectance is over 70% in the visible range. And we have successfully demonstrated a high contrast ratio over 2000:1, high quality image with a wide working temperature range from ‐30°C to 70°C.